â€œBATIKâ€ BUSINESS PRODUCTS AMONG BEFORE AND AFTER USING A DIGITAL MARKETING SYSTEM - Ambarwati, Diana; Nadhiroh, Umi (Program Pascasarjana STIE Amkop Makassar, 2020)
The purpose of this research is to analyze which batik business groups experienced the highest increase in competitiveness and product sales results and how to increase competitiveness and product sales results among before and after using a digital marketing system at one of the batik entrepreneurs. This research uses a comparative approach by analyzing the increase in the highest competitiveness and product sales results and analyze the highest competitiveness and product sales results before and after using the Digital Marketing System. The approach taken by using a questionnaire in accordance with 24 indicator variables. The study was conducted on 4 (four) Batik Business Groups in Kediri City, including Wecono Asri, Dermo, Numansa and Galuh by involving the leaders of the Batik Business Group on the company's competitiveness and product sales before and after using a digital marketing system in March and July 2019. This research technique enabled the researcher to draw conclusions based on the characteristics of respondents regarding increasing company competitiveness and product sales results. The result of this research is Batik Numansa has a higher competitiveness and sales product increase compared to Batik Wecono Asri, Dermo and Galuh. The increase in competitiveness and sales product of Batik Numansa after using a digital marketing system is higher than before using a digital marketing system Keywords : Competitiveness, Sales Result, Batik, Bussiness Product, Digital Marketing System